Regulation of financial markets in the European Union in the context of digitalisation - Lipych, Liubov; Nadeiko, Mykola (Global Prosperity, 2026)
Abstract. The article examines the evolution and current state of the regulatory architecture of the European Union’s financial markets in the context of digital transformation. The post-crisis institutional restructuring of EU financial supervision is analysed, including the establishment of the European Supervisory Authorities (EBA, ESMA, EIOPA), the formation of the Banking Union, and the introduction of the Single Rulebook concept. Key EU regulatory acts aimed at governing digital financial services are explored: the Markets in Crypto-Assets Regulation (MiCA), which for the first time globally provides comprehensive legal regulation of crypto-assets with classification into e-money tokens, asset-referenced tokens, and other crypto-tokens; the Digital Operational Resilience Act (DORA), which harmonises cybersecurity standards for the financial sector; the updated Payment Services framework PSD3/PSR, which deepens the open financial ecosystem; the AI Act, which classifies financial AI systems as high-risk; and the General Data Protection Regulation in the context of its impact on automated decision-making in finance. Regulatory approaches to fostering innovation through sandbox mechanisms, innovation hubs, and the principle of proportionality are considered. The main challenges posed by digitalisation are identified: regulatory gaps concerning decentralised finance, systemic risks of stablecoins, algorithmic bias issues, concentration of cyber risks in cloud providers, and the complexities of introducing the digital euro. The significance of the EU’s regulatory experience for Ukraine as a candidate country is substantiated. The current state of implementation of European standards in Ukraine is analysed in the areas of virtual asset regulation, open banking, banking supervision, and anti-money laundering. A strategy for gradual harmonisation with opportunities for technological leapfrogging and adaptation to wartime conditions is proposed.